Newman and Life in the Spirit : Theological Reflections on Spirituality for Today - Hughes, Brian W.; Connolly, John R. (Book collections on Project MUSE., 2014)
John Henry Newman is one of the most beloved and well-known British theologians, an instrumental figure in the Oxford Anglican movement of the nineteenth century and an infamous convert to Roman Catholicism. Through his tractates, essays, and monographs, Newman has been seen as a precursor and Father to the Second Vatican Council. His narration of his own life and conversion, Apologia pro vita sua, is often considered one of the classics of spiritual autobiography, akin to Augustine's Confessions. Newman and Life in the Spirit collects essays from leading theologians and scholars examining the theology and spirituality of one of the most important and beloved nineteenth century theologians, the recently beatified John Henry Newman. The essays in this volume present critical analysis of the perception and role of spirituality in various aspects of Newman's thought, from his doctrinal work to his university and parochial sermons, and argue for its significance to Christian theology and practice in the twenty-first century.